MODI GOVERNMENT’S HYBRID STRATEGIC POSTURE: IMPLICATIONS FOR NATIONAL SECURITY OF PAKISTAN (Margalla Papers, 2026)
Over the period, the strategic approach adopted by India towards Pakistan has characteristically recalibrated and modelled around compellence, lawfare and diplomacy. The paper examines New Delhi’s evolving posture under Prime Minister Narendra Modi, who emphasises a more audacious framework and has shifted how it manages regional security and bilateral tensions with Pakistan. Hence, it examines how it has affected Pakistan's internationality. This study draws on regional security literature, i.e., Hybrid warfare, Compellence, Diplomacy, and Law fare, to critically assess the underlying logic of India/Modi’s posture and its implications for crisis stability in the South Asian region. Moreover, this paper contextualises sequences of state actions over time, including across the Line of Control (LoC), legislative changes in Illegally Occupied Jammu & Kashmir (IIOJ&K), and coercive diplomatic engagements in multilateral forums, as part of a strategic signalling approach. Within this compellence, diplomacy, and lawfare lens, state actions empirically validate and support the literature on “hybrid warfare architecture” as an all-encompassing theoretical framework for 21st-century conflict characterised by multi-model strategic competition. Thus, the study explores whether these developments represent an enduring, strategically planned, tactically calculated and deliberately initiated transformation or merely a context-based response to security and internationality-related challenges for Pakistan. Lastly, the current integrative approach enhances conceptual clarity and promotes cross-domain analysis. The governance perspective examines the broader implications for Pakistan’s diplomatic manoeuvrability, deterrence, development and the future trajectory of Pakistan/Modi-India relations in a nuclearised environment. Bibliography EntryMirza, Sulman Naeem. 2025. "Modi Government’s Hybrid Strategic Posture: Implications for National Security of Pakistan." Margalla Papers 29 (2): 146-171.